Behavioral law and economics - Sunstein, Cass R. (Cambridge : Cambridge University Press, 2000)
This exciting volume marks the birth of a new field, one which attempts to study law with reference to an accurate understanding of human behavior. It reports new findings in cognitive psychology which show that people are frequently both unselfish and over-optimistic; that people have limited willpower and limited self-control; and that people are'boundedly' rational, in the sense that they have limited information-processing powers, and frequently rely on mental short-cuts and rules of thumb. Understanding this behavior has large-scale implications for the analysis of law, in areas including environmental protection, taxation, constitutional law, voting behavior, punitive damages for civil rights violations, labor negotiations, and corporate finance. With a better knowledge of human behavior, it is possible to predict the actual effects of law, to see how law can promote society's goals, and to reassess the questions of what law should be doing.
A behavioral approach to law and economics / Christine Jolls, Cass R. Sunstein, and Richard H. Thaler -- Context-dependence in legal decision making / Mark Kelman, Yuval Rottenstreich, and Amos Tversky -- A positive psychological theory of judging in hindsight / Jeffrey J. Rachlinski -- Behavioral economics, contract formation, and contract law / Russell Korobkin -- Organized illusions : a behavioral theory of why corporations mislead stock market investors (and cause other social harms) / Donald C. Langevoort -- Reluctance to vaccinate : omission bias and ambiguity / Ilana Ritov and Jonathan Baron -- Second-order decisions / Cass R. Sunstein and Edna Ullmann-Margalit -- Experimental tests of the endowment effect and the Coase theorem / Daniel Kahneman, Jack L. Knetsch, and Richard H. Thaler -- Assessing punitive damages (with notes on cognition and valuation in law) / Cass R. Sunstein, Daniel Kahneman, and David Schkade -- Framing the jury : cognitive perspective on pain and suffering awards / Edward J. McCaffery, Daniel J. Kahneman, and Matthew L. Spitzer -- Behavioral economic analysis of redistributive legal rules / Christine Jolls -- Do parties to nuisance cases bargain after judgment? A glimpse inside the cathedral / Ward Farnsworth -- Some implications of cognitive psychology for risk regulation / Roger G. Noll and James E. Krier -- Explaining bargaining impasse : the role of self-serving biases / Linda Babcock and George Loewenstein -- Controlling availability cascades / Timur Kuran and Cass R. Sunstein -- Cognitive theory and tax / Edward J. McCaffery.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Law and economics -- Psychological aspects